Improving Condom Self-Efficacy and Use among Individuals Living with HIV: The Positive Choices Mapping Intervention - Czuchry, Michael (2009)
Few interventions have been designed to improve behavioral outcomes and reduce risk of HIV transmission of individuals living with HIV, most focusing on preventative efforts directed at individuals who are HIV-negative. However, people living with HIV present individual and public health risks (infection with a different strain of HIV, health complications from contracting STD’s, continued sexual activity with individuals with unknown HIV status) that have become the focus of intervention efforts. The current paper explores a promising new intervention, The Positive Choices Mapping intervention (PCM), designed to increase condom self-efficacy and use among African American crack cocaine smokers who are living with HIV. The intervention was grounded in Social Cognitive Theory and incorporated an empirically backed visual representation strategy (node-link mapping). The focus of the current paper is on the main components of the intervention.